Pengaruh Net Profit Margin, Debt To Equity Ratio, Perputaran Piutang Dan Perputaran Kas Terhadap Roa Pada Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2019 - Vincent Fahry; Dewi Gunawan; Cindy Meilianti; Mohd Nawi Purba (Journal of Economic, Bussines and Accounting (COSTING), 2021)
The aims of this study to analyze and examine how the influence of NPM, DER, Accounts Receivable Turnover and Cash Turnover on ROA in various industrial sectors listed on the Indonesia Stock Exchange 2016-2019 Period. The populations is 51 companies in the automotive sector listed on the IDX for the period 2016-2019 and obtained a sample of 20. Purposive sampling was the sampling technique of this study. The method used in this research is quantitative method, the nature of the research used is explanatory or explanatory, and uses data collection techniques in the form of documentation, types, and data sources in the form of financial reports of various industrial subsectors listed on the IDX 2016-2019. Keywords : Net Profit Margin, Debt To Equity Ratio, Accounts Receivable Turnover, Cash Turnover, Return On Assets